RANCANG BANGUN LAMPU OTOMATIS UNTUK TANAMAN BUAH NAGA BERBASIS SMART AGRICULTURE - Abdul Qodir; Lie Jasa; Wayan Gede Ariastina (Program Studi Teknik Elektro UNUD, 2025)
Indonesia is an agrarian country rich in agricultural commodities, one of which is dragon fruit. Dragon fruit has high economic value and health benefits. However, the productivity of dragon fruit plants is greatly influenced by the duration and intensity of sunlight, which becomes a challenge during the rainy season or days with low light intensity. This study aims to design an automatic lighting control system based on a microcontroller with On/Off scheduling features to support dragon fruit cultivation in Krajan Village, Yosomulyo Village, Banyuwangi Regency. This system utilises Internet of Things (IoT) technology and the NTP protocol for time synchronisation, enabling real-time monitoring of sensors and lighting control without direct user intervention. The method used involved the design and testing of the microcontroller from January to February 2025. Test results indicate that the use of yellow LED lights can enhance flowering and plant growth by extending photosynthesis duration, particularly at night. Thus, this system effectively increases dragon fruit productivity and quality while providing an efficient solution for farmers facing natural lighting limitations.